An invisible villain: high perceived stress, its associated factors, and possible consequences in a population-based survey in southern Brazil - Demenech,Lauro Miranda (2022)
Abstract Introduction Much of the evidence on the relationship between stress, lifestyle, and other physical and mental health outcomes comes from studies conducted in high-income countries. There is therefore a need for research among populations in low and middle-income settings. Objectives To measure stress levels and identify factors associated with a high stress level and its consequences for health. Methods This was a population-based cross-sectional study carried out in 2016 with adults aged 18 years or older in a municipality in southern Brazil. A two-stage sampling strategy based on census tracts was used. Stress levels were measured with the Perceived Stress Scale (PSS-14) and classified into quartiles. The impact of the highest stress levelon each outcome was assessed with etiologic fractions (EF). Results The most stressed groups were: females (PR = 1.51, 95%CI 1.25-1.81), younger people (PR = 1.76, 95%CI 1.26-2.46), middle-aged individuals (PR = 1.60, 95%CI 1.17-2.19), those with lower schooling (PR = 1.56, 95%CI 1.20-2.02), the physically inactive (PR = 1.51, 95%CI 1.20-1.91), people who spent three or more hours watching television per day (PR = 1.29, 95%CI 1.12-1.50), and those with food insecurity (PR = 1.44, 95%CI 1.19-175). Possible consequences of high stress level were regular or poor self-perception of health (EF = 29.6%), poor or very poor sleep quality (EF = 17.3%), lower quality of life (EF = 45.6%), sadness (EF = 24.2%), and depressive symptoms (EF = 35.8%). Conclusions Stress plays an important role in several domains of health. Both public policies that target reduction of inequalities and specific stress-management interventions can reduce stress levels in populations, thereby decreasing the burden of other negative physical and mental health outcomes related to stress.